PERENCANAAN PEMANENAN AIR HUJAN SEBAGAI ALTERNATIF PENYEDIAAN KEBUTUHAN AIR BERSIH (STUDI KASUS DESA PELEHU KEC. BILATO KAB. GORONTALO) - Kamal Purnomo Miu Kamal Purnomo Miu; Rawiyah Husnan; Barry Yusuf Labdul (Composite Journal, 2022)
Limited water resources in coastal areas is a problem often encountered, with high rainfall intensity being one of the most potent factors to solve it. Pelehu Village is one of regions located in Gorontalo District, a coastal area that was experiencing said problem. Rain intensity is one of the parameters used in calculating the discharge, in wich a proper analysis method based on Bubaa Drainage Basin at Paguayamn Pantai is necessary. The quality of the rainwater that will be used should also be qualified by the water characteristics based on the quality standards, in wich water samples to test the parameters of Chemistry, Physic, and Bacteriology are required. Rainwater harvesting installation system also requires planning and budget planning; therefore, this research aimed to analyze rainwater potential, water characteristics, and rainwater harvesting installation budget plan in Pelehu Village. The inhabitants’ needs for water were calculated based on the projected population growth from 2021 to 2025. Rainfall intesity was analyzed uaing Normal, Log-Normal, Log Pearson III, and Gumbel distributions, while the method used to analyze the rainfall intensity was Mononobe. The rainfall data were retrieved from Bubaa Drainage Basin at Paguyaman Beach for the last seven years. The tested characteristics of rainwater are mandatory Physical, mandatory Chemical, and Bacteriology parmeters based on the quality standard im Permenkes No. 32 of 2017. Budget plan was calculated based on the planning of rainwater harvesting instalation in Pelehu Village Office. The analysis of population growth from 2021 to 2025 is 833, 853, 874, 895, and 917 people, with 66.624, 68.247, 71.611, 73.355 liters/day of water needs amount. The value of Cv, Cs, and Ck of rainfall intensity analysis result of the statistical parameters were 0,84, 3, and 0,2, respectively; hence, the most compatible distribution pattern was the Log Pearson III. The highest precipitation intensity occured in five minutes for return periods of 100 years, wich was 197,75 mm/h. Water discharge was calculated with the rational method of 0,8420 m3/ sec ≈ 824,027 liters/sec. The rainwater potential in the village is 2966,4975 m3/h ≈ 2.966.498 liters/hour. The rainwater characteristics have met the quality standards for the parameters of Chemistry, Physics, and Bacteriology based of Permenkes No. 32, 2017. The budget plan of rainwater harvesting installation is Rp. 6.219.000 (Six Million Two Hundred Nineteen Thousand Rupiah).